(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: We planned to assess the serum ferritin levels among ischemic stroke cases and to correlate it with early neurological deterioration and prognosis of acute ischaemic stroke and to find the relationship between serum ferritin and various risk factors for Stroke. Methods: This study was conducted as a cross sectional observational study among patients attending outpatient and inpatient department of General medicine, Neurology and emergency with acute ischemic stroke during August 2022 – November 2022 in Chettinad medical Center Hospital in Chennai. A total of sixty patients with acute ischemic stroke were included in this study. All data was entered in excel sheet and analyzed using SPSS. Results: A significant association between high levels of serum ferritin and severe and poor prognosis cases with acute ischemic stroke. Also, we noted significant rise in serum ferritin in ischemic stroke patients in correlation with high scores with NIHSS which indicates the severity. This study also reveals the poor outcome in correlation with high serum ferritin values and good outcome in correlation with low serum ferritin values, based on Modified Rankin scale. Also, diabetes mellitus and systemic hypertension, alcohol consumption and loss of consciousness were found to be associated with serum ferritin levels, in this study. Conclusion: Increased serum ferritin is linked with poor outcome in AIS cases. Hence more focus to be paid on cases with high serum ferritin and all cases with AIS should be assessed for serum ferritin routinely.